2012
DOI: 10.1128/iai.05702-11
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Roles of Human Carcinoembryonic Antigen-Related Cellular Adhesion Molecules during Neutrophil Responses to Neisseria gonorrhoeae

Abstract: Symptomatic infection of humans with Neisseria gonorrhoeae is characterized by a neutrophil-rich cervical or urethral exudate, suggesting that neutrophils are important both for the clearance of these bacteria and for the pathogenesis of gonorrhea. Neisseria interacts with neutrophils through ligation of human carcinoembryonic antigen related-cellular adhesion molecules (CEACAMs) by their surface-expressed Opa proteins, resulting in bacterial binding, engulfment, and neutrophil activation. Multiple CEACAMs are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
108
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(118 citation statements)
references
References 45 publications
7
108
1
2
Order By: Relevance
“…6A). This is in agreement with previous results, showing that CEACAM3 engagement, but not CEACAM1 binding, by Opa CEA proteins is critical for efficient opsonin-independent uptake by human granulocytes (13,34,41). Furthermore, binding of MS11 Opa CEA-a proteins to CEACAM3 is known to trigger the production of reactive oxygen species by granulocytes and finally results in the destruction of the bacteria (34,42).…”
Section: Resultssupporting
confidence: 81%
“…6A). This is in agreement with previous results, showing that CEACAM3 engagement, but not CEACAM1 binding, by Opa CEA proteins is critical for efficient opsonin-independent uptake by human granulocytes (13,34,41). Furthermore, binding of MS11 Opa CEA-a proteins to CEACAM3 is known to trigger the production of reactive oxygen species by granulocytes and finally results in the destruction of the bacteria (34,42).…”
Section: Resultssupporting
confidence: 81%
“…Characterization of individual CEACAM function in neutrophilic cell lines showed that Opa-mediated neutrophil activation is mediated by CEACAM3 signaling, while CEACAM1 and CEACAM6 allowed bacterial internalization without triggering production of reactive oxygen species (ROS) or release of toxic granule proteins (44). However, all of the studies focusing on neutrophil responses to Opa-CEACAM binding have been done exclusively with the commonly studied N. gonorrhoeae strains MS11 (44,45,47,61,62) and FA1090 (63,64).…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that the high prevalence of Opa expression in our LPCIs suggests that Opa proteins facilitate infection. However, since each Opa variant may have a different spectrum of CEACAM binding, since the spectrum of binding has the potential to drastically affect the host cellular response to infection (28,30,32,38,43,44,47), and since the pattern of CEACAM expression varies between sexes and cell types, we sought to characterize the binding specificity of each N. gonorrhoeae isolate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To measure survival of gonococci in the presence of PMNs, an Opacity protein (Opa)-negative mutant of N. gonorrhoeae strain FA1090 that was grown in media containing 2 μg/ml CMP-Neu5Ac to sialylated LOS was added to 1 × 10 6 PMNs at a multiplicity of infection (MOI) of 10 (10 bacteria to 1 PMN). Opa-negative N. gonorrhoeae was used because select Opa proteins serve as ligands for human carcinoembryonic antigenrelated cell adhesion molecule 3 (CEACAM3) that is expressed by PMNs and results in phagocytosis (38). FHD1119G/HuFc was added at a concentration of 16.7 μg/ml, followed by 10% human complement (prepared as described above).…”
Section: Opsonophagocytosis Assaymentioning
confidence: 99%